Introduction to Hardware Security and Trust - Tehranipoor, Mohammad; Wang, Cliff (Springer New York : Imprint: Springer, 2012)
The emergence of a globalized, horizontal semiconductor business model raises a set of concerns involving the security and trust of the information systems on which modern society is increasingly reliant for mission-critical functionality. Hardware-oriented security and trust issues span a broad range including threats related to the malicious insertion of Trojan circuits designed, e.g.,to act as a 'kill switch' to disable a chip, to integrated circuit (IC) piracy,and to attacks designed to extract encryption keys and IP from a chip. This book provides the foundations for understanding hardware security and trust, which have become major concerns for national security over the past decade.  Coverage includes security and trust issues in all types of electronic devices and systems such as ASICs, COTS, FPGAs, microprocessors/DSPs, and embedded systems.  This serves as an invaluable reference to the state-of-the-art research that is of critical significance to the security of,and trust in, modern society's microelectronic-supported infrastructures. Provides a comprehensive introduction to hardware security and trust; Includes coverage at the circuit and systems levels, with applications to design and implementation; Describes a variety of state-of-the-art applications, such as physically unclonable functions, unclonable RFID tags and attack and countermeasures for smart cards.